The dissonant care management of illicit drug users in medical wards, the views of nurses and patients: a grounded theory study. (8th July 2012) - Monks, Rob; Topping, Annie; Newell, Rob
Abstract Aims The aim of this study was to explore how registered nurses manage and deliver care to patients admitted to medical wards and Medical Assessment Units with complications of drug use and to elicit the experiences and views of those receiving that care. Background Illicit drug use is a major public health problem worldwide. The physical complications of problem drug use often result in admission to medical wards. Registered nurses working in these settings have been reported as possessing negative attitudes towards patients who use illicit drugs and lacking preparation to provide problem drug use–related care needs. Design Grounded theory. Methods A grounded theory approach was used to collect and analyse 41 semi‐structured interviews. Data collection and analysis were undertaken in nine medical wards in the Northwest of England in 2008. A combination of purposive and theoretical sampling was adopted to recruit registered nurses (n = 29) and medical ward patients (n = 12) admitted for physical complications of problem drug use. Data were subjected to constant comparative analysis. Findings Two sub‐categories emerged: 'Lack of knowledge to care' and 'Distrust and detachment' and these formed the core category 'Dissonant care'. The combination of lack of educational preparation, negative attitudes and experience of conflict, aggression, and untrustworthiness appeared to affect negatively the nurse–patient relationship. Conclusions This study illuminated interplay of factors that complicated the delivery of care. The complexity of caring for patients who are pre‐judged negatively by nurses appears to engender dissonance and disparities in care delivery. Better education and training, coupled with role support about problem drug use may reduce conflict, disruption, and violence and facilitate competent care for these patients.